Terapi Relaksasi Otot Progresif Sebagai Intervensi Non-Farmakologis untuk Merurunkan Kecemasan pada Penderita Hipertensi - Fihlia Hardiyantika; Wachidah Yuniartika (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2026)
Hypertension is a chronic, non-communicable disease with a continuously increasing prevalence rate and often causes psychological impacts, including anxiety. To control the problem, effective non-pharmacological interventions are needed, one of which is progressive muscle relaxation (PMR) therapy. The purpose of this study is to evaluate the effect of PMR on anxiety levels in hypertensive patients. This research is a quantitative study with a quasi-experimental design of two groups, pre-test post-test with a control group. The sampling technique used was total purposive sampling with 32 respondents, 16 in the control group and 16 in the treatment group, to assess anxiety levels before and after PMR administration. The study instrument used the Zung Self-Rating Anxiety Scale questionnaire, with a validity test result of r greater than 0.33. The educational media used in the study were PMR flashcards. PMR intervention was conducted four times a week for three weeks, with each therapy session lasting 15-20 minutes. The research results showed a P-value of 0.001, with pre-control mean values of 43.06, post-control 49.69, pre-treatment 43.31, and post-treatment 42.38. The results indicated a significance value less than 0.05. The results show a difference between the initial and final variables, leading to the conclusion that PMR administration affects the reduction of anxiety in hypertensive patients. These results are also in line with Raziansyah's and Sayuti’s (2022) study, which states that PMR is effective in reducing anxiety levels from severe to moderate, with a statistical result of p<0.05.